Spin-dependent thermoelectric effects in Fe-C6 doped monolayer MoS2 - Lin Zhu (Nature Portfolio, 2017)
Abstract By using the non-equilibrium Green’s function with density functional theory, we have studied the thermal spin transport properties of Fe-C6 cluster doped monolayer MoS2. The results show that the device has a perfect Seebeck effect under temperature difference without gate voltage or bias voltage. Moreover, we also find the thermal colossal magnetoresistance effect, which is as high as 107%. The competition between spin up electrons and spin down holes of the parallel spin configuration leads to peculiar behavior of colossal magnetoresistance and thermo-current, which is essential for the design of thermal transistors. These results are useful in future MoS2-based multifunctional spin caloritronic devices.